KAJIAN MENGENAI KAMPUNG BATIK SEBAGAI PEREMAJAAN KEMBALI KAMPUNG DI KAWASAN KARET KUNINGAN - Steven Wijaya; Timmy Setiawan (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Millennials have become an important topic in various discussions at the beginning of the 21st century with a population that is currently in productive age and has a greater global number. However, the beginning of the millennial generation in Indonesia began with the 1998 crisis, where this will affect the decline in the level of education of the early millennial generation in Indonesia. Education and a low economy make the competitiveness of human resources in some regions, in this case it will increase in the lives of villages in the city of Jakarta, where the difference in life is very contrasting between those who get higher education and those who get low education (in rural areas). So the question is how can the generation of melenial living in the city of Jakarta compete and how to rejuvenate urban settlements, especially Jakarta, so that the millennial generation in the village can compete and adapt in the next generation? Every village must have its own characteristics and high historical value. As the development and recovery of the times, the characteristics and historical values of the village are often forgotten by the people, so the village no longer has an identity that they can be proud of. So the program was needed to restore the distinctive characteristics of a village by inviting residents from the village to be involved in it, so that the uniqueness and precision that could be of benefit both in terms of economy, development, and human resources in the village. In this way the position of the village in the middle of the city can remain by providing positive for the residents in the house with outsiders around it. By raising the characteristic of the village, the millennial in the village can compete and still be able to maintain its existence.Abstrak Generasi milenial menjadi topik penting dalam berbagai diskusi di awal abad 21, kerana jumlah populasinya yang tengah berada di usia produktif dan memiliki jumlah terbesar secara global. Namun, awal generasi milenial di Indonesia dimulai dengan krisis moneter tahun 1998, dimana hal ini akan berpengaruh terhadap menurunnya tingkat pendidikan generasi milenial awal di Indonesia. Pendidikan dan perekonomian yang rendah membuat daya saing sumber daya manusia di beberapa daerah juga menurun, dalam kasus ini akan difokuskan pada kehidupan perkampungan di Kota Jakarta, dimana perbedaan kehidupan sangat-lah kontras antara yang memperoleh pendidikan tinggi dengan yang memperoleh pendidikan rendah (daerah perkampungan). Sehingga yang menjadi pertanyaan adalah bagaimana cara generasi melenial yang hidup di perkampungan kota Jakarta dapat bersaing dan bagaimana meremajakan kembali perkampungan di perkotaan khususnya Jakarta, agar generasi milenial di perkampungan tersebut dapat bersaing dan beradaptasi dalam generasi selanjutanya? Setiap perkampungan pastinya memiliki ciri khas dan nilai sejarah yang tinggi. Seiring dangan perkembangan dan tuntutan zaman, ciri khas dan nilai sejarah dari kampung itu sering dilupakan oleh warganya, sehingga suatu kampung tidak lagi memiliki identitas yang dapat mereka banggakan.  Maka diperlukalah program untuk memulihkan kembali ciri khas dari suatu kampung dengan mengajak warga dari kampung tersebut untuk turut terlibat di dalamannya, sehingga keunikan dan cirikhas itu bisa menjadi manfaat baik dalam segi ekonomi, kebudayaan, dan sumber daya manusia di kampung tersebut. Dengan cara inilah kedudukan kampung ditengah kota dapat tetap bertahan dengan memberikan dampak positif bagi penghuni yang ada didalam kampung tersebut maupun dengan orang-orang luar yang ada di sekitarnya. Sehingga dengan menonjolkan sebuah cirikhas, generasi milenial yang tinggal di kampung tersebut dapat bersaing dan tetap dapat mempertahankan eksistensinya.